(untitled) (Proceedings OPTIMAL, 2025)
Malnutrition in toddlers remains a major public health challenge, particularly in low-income communities where access to diverse and nutrient-rich foods is limited. Purple sweet potato (Ipomoea batatas L.) is a local, affordable, and nutrient-dense food that holds potential as a complementary food for children under five. This study aimed to assess the effectiveness of supplementary feeding (PMT) using purple sweet potato porridge in improving the weight of toddlers in Kelurahan Pojok, Indonesia. A quasi-experimental design with a one-group pretest-posttest approach was used, involving 30 toddlers aged 12–36 months. The intervention consisted of 100 grams of purple sweet potato porridge given daily for 14 days. Weight measurements were taken before and after the intervention. The average weight increased from 9.8 ± 1.2 kg to 10.2 ± 1.3 kg, with a statistically significant gain (p = 0.002). The results suggest that purple sweet potato-based PMT is effective in improving toddler weight and can be implemented as a community-based intervention. This approach supports food security, utilizes local agricultural products, and empowers families to contribute to child nutrition programs.